Blue, Rather Than Red Light Can Nudge Employees to Choose Delayed But Larger Wage Payment. Issue 9 (November 2022) - Geng, Xiaowei; Zhang, Kai; Ma, Jiatao; Yang, Huiming; Chen, Ziguang; Li, Shu
Most businesses have been severely affected during the ongoing Coronavirus Disease 2019 (COVID-19) pandemic, as they lack sufficient cash reserves for turnaround in this devastated business environment. This study presents a nudge-based approach for encouraging employees to choose delayed but larger wage payment. Through two laboratory experiments and one field experiment, we found that blue light more likely promotes individuals choosing the farsighted intertemporal option (i.e., delayed but larger payment) than red light. We further investigated why blue light can promote such a farsighted decision and found that the intradimensional difference comparison —that is, comparing the difference between the two options in the time dimension (∆ time A, B ) and the difference in the payoff dimension (∆ payoff A, B )—mediates the effect of blue (vs. red) light on intertemporal choice. The current study demonstrates the effectiveness of light color and provides a solution to nudge people to make farsighted choices.